Проблеми та виклики соціальній політиці Європейського Союзу у контексті міграційної кризи - Івасечко, Ольга; Здоровега, Мар’яна; Ivasechko, Olga; Zdoroveha, Mariana (Lviv Politechnic Publishing House, 2017)
Досліджено проблеми та виклики соціальної політики ЄС у контексті міграційної кризи. Акцентовано увагу на тому, що збереження динаміки напливу біженців та подальша ескалація міграційної кризи у найближчій перспективі може стати причиною ще більшого зростання економічних видатків через необхідність фінансування соціальної політики ЄС, яке проводиться з бюджетів країн-членів, як наслідок – тягар міграційної кризи лягає на громадян-платників податків, які проживають у межах Європейського Союзу.

Problems and challenges of EU social policy in the context of migration crisis are considered in the article. An attitude of individual member states to the migration crisis in Europe is researched. It has been determined that nowadays EU social policy remains a vulnerable area that requires a comprehensive unified approach and appropriate support to all itsmember states. The emphasis is placed on the fact that preserving dynamics of the influx of refugees and further escalation of the migration crisis could increase economic costs due to the necessity of financing EU social policy from the budget of EU member states. As a result, migration crisis burden falls on taxpayers, who reside within the European Union. Moreover, increasing the number of refugees may lead to an additional pressure on the labor market in European countries and further intensifying an unemployment problem in Europe. It is evident that such problems are not for the benefit of EU citizens, which, in turn, will cause an aggravation of interethnic confrontations and deterioration of an attitude towards foreign migrants. European citizens expect the specific objectives of common EU social policy in order to maintain peace and security, fight against unemployment, all forms of crime and organized drug trafficking, to reduce poverty, ensure equality between men and women, and for protecting the environment, quality and safety of products. To support the balance and participation of EU citizens in the European project, the EU should strengthen and reinforce integration in the social sphere. The author draws conclusions and suggests that development of EU social policy in the future will focus on the position, according to which until the end of this decade, Europe will put its main forces on solving internal development problems and will stay in the area of high economic, social and political risks. This is a painful revision of the social market model, aimed at increasing competitiveness in order to take a leading position in the 21st century. It is determined that these challenges arising from difficulties in implementing the Europe 2020 strategy. The main obstacles are legislation at the national level and the lack of implementation of agreements at the EU level.
Problems and challenges of EU social policy in the context ofmigration crisis
Keywords: соціальна політика; Європейський Союз; міграція; міграційна криза; біженці; міграційна політика; social policy; the European Union; migration; migration crisis; refugees; migration policy; 327.7; 314.1